STRATEGI PEMASARAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) KULINER BERBASIS LOKAL DI KOTA MAKASSAR - Harwianti Santoso, Siti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Amid intense culinary sector competition in Makassar City, local-based marketing strategies emerge as vital for MSMEs to leverage cultural identity and traditional recipes for competitive advantage. This study aims to analyze these strategies' implementation and impact on business competitiveness and sustainability. Employing a qualitative descriptive approach, purposive sampling targeted culinary MSME owners utilizing local elements, with researchers as primary instruments complemented by semi-structured interview guides, observation protocols, and documentation. Data analysis followed Miles and Huberman's interactive model involving reduction, presentation, and conclusion drawing, validated through source and method triangulation. Findings reveal strategies encompassing local cultural identity in branding, traditional recipes, regional raw materials, culturally-themed packaging, and digital storytelling, strengthening brand image, consumer trust, and loyalty while enhancing competitiveness. In conclusion, local-based marketing proves an effective, sustainable approach for Makassar culinary MSMEs, balancing economic growth with cultural preservation.